Experimentation and innovation: purpose, possibilities and preferred solutions - Judy Matthews (CERN IdeaSquare Journal of Experimental Innovation, 2017)
This paper explores the range of purposes for  experimenting and identifies some of the patterns and processes where experimentation leads to innovation. Thematic analysis of a brief overview of literature indicates that experimentation can be understood from multiple perspectives: as a mindset, a determination to solve a puzzle or challenge, a generic research process to develop new goods and services, to explore new fields and as a core process in creating desired futures. Experimentation will increase in importance as researchers and organisations explore dynamic and turbulent environments, seeking new avenues to generate and apply new technologies, and capture their benefits.